1998
DOI: 10.1159/000013996
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone, Insulin-Like Growth Factor-I and Insulin-Like Growth Factor Binding Protein-3 Are Regulated Differently in Small-for-Gestational-Age and Appropriate-for-Gestational-Age Neonates

Abstract: Growth hormone (GH), insulin-like growth factor-I (IGF-I) and IGF-binding protein-3 (IGFBP-3) were measured in 90 neonates during the first 5 days of life. Twenty-six small-for-gestational-age (SGA) neonates were compared with 64 appropriate-for-gestational-age (AGA) neonates. There were no differences in nutritional status between the 2 groups. Mean GH levels were significantly higher in the SGA group (53.4 ± 30.8 vs. 39.9 ± 23.3 µg/l; p < 0.05). In both groups GH levels correlated with birth weight (expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 20 publications
0
22
1
3
Order By: Relevance
“…A study of normal children found that lower birth weight and IGF1 concentrations were associated with poor compensatory insulin secretion, suggesting a link between early somatotropic axis regulation and later metabolic derangement; these effects were independent of postnatal growth (22). Growth-restricted infants are also reported to have perturbed somatotropic axis regulation in the postnatal period independent of current nutritional status and have a higher rate of later metabolic disease (23). LBW followed by rapid growth in childhood is associated with the worst health outcomes in later life (24), including glucose intolerance, cardiovascular disease, and obesity (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…A study of normal children found that lower birth weight and IGF1 concentrations were associated with poor compensatory insulin secretion, suggesting a link between early somatotropic axis regulation and later metabolic derangement; these effects were independent of postnatal growth (22). Growth-restricted infants are also reported to have perturbed somatotropic axis regulation in the postnatal period independent of current nutritional status and have a higher rate of later metabolic disease (23). LBW followed by rapid growth in childhood is associated with the worst health outcomes in later life (24), including glucose intolerance, cardiovascular disease, and obesity (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Fasting stimulates GH release in humans and infants with IUGR who characteristically show elevated basal levels of GH (Leger et al 1996, Cance-Rouzaud et al 1998. It has been unclear, however, what factors specifically activate this system in undernutrition.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was attributed to the state of undernutrition of these fetuses and a role for ghrelin in fetal adaptation to intrauterine malnutrition has been proposed (125,126). Furthermore, fasting is known to stimulate GH release in infants with IUGR, who characteristically show elevated basal levels of GH (127). Therefore, the augmented ghrelin concentrations in IUGR may consequently lead to elevated GH concentrations, as ghrelin has a potent GH-releasing activity (122).…”
Section: Ghrelin In Iugrmentioning
confidence: 99%